PENGEMBANGAN LKPD UNTUK MENINGKATKAN VALIDITAS KETERAMPILAN MENULIS TEGAK BERSAMBUNG PADA PEMBELAJARAN BAHASA INDONESIA KELAS LL SDN 01 ULAK SELATAN - Jayanti; Ayunis; Nofriza Efendi; Gusnita Efrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of cursive handwriting skills among Grade II students at SDN 01 Ulak Selatan, which was caused by the lack of engaging, systematic, and age-appropriate instructional materials. The study aimed to develop Student Worksheets (LKPD) with a high level of validity as instructional materials to support the improvement of students' cursive handwriting skills in Indonesian language learning. This research employed a Research and Development (R&D) method using the Borg and Gall development model, which includes the stages of research and information gathering, planning, preliminary product development, expert validation, product revision, limited field testing, field testing, final revision, and dissemination. The research subjects were Grade II students of SDN 01 Ulak Selatan. The research instruments consisted of expert validation sheets, teacher and student response questionnaires, observation sheets, and cursive handwriting skill tests. The results indicated that the developed LKPD achieved a validity score of 91.25%, categorized as highly valid, a practicality score of 93.75%, categorized as highly practical, and an observer validation score of 91.66%, also categorized as highly valid. Furthermore, the implementation of the LKPD contributed to improving students' cursive handwriting skills through systematic, engaging, and developmentally appropriate learning activities. Therefore, the developed LKPD is considered feasible and appropriate for use as a supporting instructional material in Indonesian language learning for Grade II elementary school students.